2015
DOI: 10.18410/jebmh/2015/727
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Changes of GFR in a Population of Kerala

Abstract: BACKGROUND: Glomerular Filtration Rate (GFR) is the best index for assessing kidney function. Ethnicity has a potential influence on GFR. Anatomic and physiological changes of ageing kidney influences GFR. AIMS AND OBJECTIVES: To find age related variations of GFR in a population of Kerala. SUBJECTS AND METHODS: A total of 519 subjects of all ages from the community were screened. Blood pressure, diabetes, mellitus, proteinuria, serum creatinine being checked. Estimated GFR (e GFR) assessed using modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The donor profile in terms of age, female predominance in our study is with earlier reports from India. [1,2,4,5,7,9,10] The eGFR by DTPA method (Gates method) ranged from 56-117 ml/min, with mean and standard deviation of 84.56 ml/min and 11.60 respectively. The range and mean eGFR in our study is consistent with other India studies which reported the mean eGFR (Gates method) of 61 to 119.34 ml/min.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The donor profile in terms of age, female predominance in our study is with earlier reports from India. [1,2,4,5,7,9,10] The eGFR by DTPA method (Gates method) ranged from 56-117 ml/min, with mean and standard deviation of 84.56 ml/min and 11.60 respectively. The range and mean eGFR in our study is consistent with other India studies which reported the mean eGFR (Gates method) of 61 to 119.34 ml/min.…”
Section: Discussionmentioning
confidence: 99%
“…The range and mean eGFR in our study is consistent with other India studies which reported the mean eGFR (Gates method) of 61 to 119.34 ml/min. [1][2][3][4][5][6][7][8][9][10] The GFR in healthy Indian is lower than western population with different studies reporting the mean eGFR from 119 to 130 ml/min. [11,12] The mean eGFR in South Korean was reported as 77.1 ml/min with SD of 16.3, which is similar to mean eGFR from Indian studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical behavior of coir reinforced polyester composite was investigated by Kuriakose et al . They observed the effect of the reinforcement structure and its surface treatment on it.…”
Section: Coir Fiber‐reinforced Composites and Their Propertiesmentioning
confidence: 99%